British Society of Gastroenterology guidelines on the management of irritable bowel syndrome. Issue 7 (26th April 2021) - Vasant, Dipesh H; Paine, Peter A; Black, Christopher J; Houghton, Lesley A; Everitt, Hazel A; Corsetti, Maura; Agrawal, Anurag; Aziz, Imran; Farmer, Adam D; Eugenicos, Maria P; Moss-Morris, Rona; Yiannakou, Yan; et al.
Abstract : Irritable bowel syndrome (IBS) remains one of the most common gastrointestinal disorders seen by clinicians in both primary and secondary care. Since publication of the last British Society of Gastroenterology (BSG) guideline in 2007, substantial advances have been made in understanding its complex pathophysiology, resulting in its re-classification as a disorder of gut-brain interaction, rather than a functional gastrointestinal disorder. Moreover, there has been a considerable amount of new evidence published concerning the diagnosis, investigation and management of IBS. The primary aim of this guideline, commissioned by the BSG, is to review and summarise the current evidence to inform and guide clinical practice, by providing a practical framework for evidence-based management of patients. One of the strengths of this guideline is that the recommendations for treatment are based on evidence derived from a comprehensive search of the medical literature, which was used to inform an update of a series of trial-based and network meta-analyses assessing the efficacy of dietary, pharmacological and psychological therapies in treating IBS. Specific recommendations have been made according to the Grading of Recommendations Assessment, Development and Evaluation system, summarising both the strength of the recommendations and the overall quality of evidence. Finally, this guideline identifies novel treatments that are in development, as well as highlighting areas of unmet need for future research.